A Cholesterol Biosensor Based on the NIR Electrogenerated-Chemiluminescence (ECL) of Water-Soluble CdSeTe/ZnS Quantum Dots. (1st March 2015) - Stewart, Alasdair J.; O'Reilly, Emmet J.; Moriarty, Roisin D.; Bertoncello, Paolo; Keyes, Tia E.; Forster, Robert J.; Dennany, Lynn
Graphical abstract: ABSTRACT: This contribution examines the application of near infra-red (NIR) quantum dot (QD) containing films for cholesterol detection. Water-soluble, 2-(dimethylamino) ethanthiol (DAET) protected 800 nm CdSeTe/ZnS core-shell QDs were prepared and incorporated into a chitosan film. The NIR electrogenerated chemiluminescence (ECL) of the QD/chitosan films upon reaction with H2 O2 co-reactant (produced as a by-product of cholesterol oxidase-catalysed oxidation of cholesterol) gave a strong ECL signal at −1.35 V vs. Ag/AgCl. The sensor displayed a linear response over the clinically relevant range (0.25 ≤ [cholesterol] ≤ 5 mM) allowing the rapid detection of cholesterol and providing a platform for future development. Significantly, this NIR emission has been shown to exhibit excellent penetrability through biological samples, and will likely be at the forefront of development in the biosensing and imaging fields for the foreseeable future.